Efeito da orientação alimentar sobre o perfil nutricional em pessoas vivendo com Aids - FERNANDES, Jessica Figueira Lima (2023)
The Human Immunodeficiency Virus (HIV) spreads through bodily fluids and attacks the immune system, specific cells such as CD4+ T lymphocytes. With the frequent attack, the defense cells start to function less efficiently until they are destroyed. With a weak body and low immunity, opportunistic diseases appear, leading to the most advanced stage of the disease, AIDS. Global statistics show that, by the end of 2019, there were more than 38 million people in the world living with HIV, with an incidence of 1.7 million. A highly potent antiretroviral therapy was introduced in the 1990s, aimed at slowing the progression of immunodeficiency and/or restoring immunity to the infected person. Regardless of the stage of the disease at which you know yourself, people living with HIV are at nutritional risk. Therefore, the World Health Organization (WHO) recommends that a nutritional intervention participate in all control and treatment programs to improve adherence and effectiveness of antiretroviral therapy, as it contributes to reducing opportunistic adjustments, helps to maintain the defense system of antiretroviral therapy. organism, providing a good quality of life to the individual. The aim of this study was to evaluate the effect of dietary guidance on the nutritional profile of people living with AIDS. It consists of an intervention study carried out in a university hospital in the city of Belém-Pa, where 25 patients living with AIDS using antiretroviral therapy were obtained. Data collection was carried out in 2 phases. Phase 1 consisted of the characterization of the clinical nutritional profile, where patients were obtained through an anthropometric assessment and sociodemographic and behavioral reports, after which the nutritional intervention was carried out through nutritional guidance based on the Food Guide for a Brazilian population. Phase 2 consisted of reassessing these patients 3 months later. It resulted in the reduction of only one variable (BMI), an important instrument for classifying nutritional status. It is necessary to apply other more effective interventions, such as an individualized eating plan, in addition to other guidance instruments, so that there is a more expressive change in the variables.